The Influence of Personality Traits and Sharing Economy Participation on Impulsive Buying Behavior among University Students - Anfas; Arifuddin Mas'ud; Hendrian; Julia Safitri (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Impulsive buying behavior has become increasingly prevalent among university students in the digital era, as spontaneous purchasing is shaped by the interaction of psychological factors such as personality traits and socio-digital engagement through sharing economy platforms. This study aims to examine the influence of personality traits and sharing economy participation on impulsive buying behavior among students. Employing a quantitative approach with a causal-associative design, the study involved the university students with samples selected through purposive sampling. Data were collected using a five-point Likert scale questionnaire and analyzed through multiple linear regression using SPSS. The results reveal that both personality traits and sharing economy participation have positive and significant partial effects on impulsive buying behavior. However, when tested simultaneously, these variables account for only 6.9% of the variance in impulsive behavior, while the remaining 93.1% is influenced by other factors. These findings confirm that students’ impulsive behavior is a multidimensional phenomenon, shaped not only by personality and digital engagement but also by complex emotional and social dynamics.